Improvement in B1+ Homogeneity and Average Flip Angle Using Dual-Source Parallel RF Excitation for Cardiac MRI in Swine Hearts - Schär, Michael; Ding, Haiyan; Herzka, Daniel A. (PloS one, 2015)
Cardiac MRI may benefit from increased polarization at high magnetic field strength of 3 Tesla but is challenged by increased field inhomogeneity. Initial human studies have shown that the radiofrequency (RF) excitation field (B1+) used for signal excitation in the heart is both inhomogeneous and significantly lower than desired, potentially leading to image artifacts and biased quantitative measures. Recently, multi-channel transmit systems have been introduced allowing localized patient specific RF shimming based on acquired calibration B1+ maps. Some prior human studies have shown lower than desired mean flip angles in the hearts of large patients even after RF shimming. Here, 100 cardiac B1+ map pairs before and after RF shimming were acquired in 55 swine. The mean flip angle and the coefficient of variation (CV) of the flip angle in the heart were determined before and after RF shimming. Mean flip angle, CV, and RF shim values (power ratio and phase difference between the two transmit channels) were tested for correlation with cross sectional body area and the Right-Left/Anterior-Posterior ratio. RF shimming significantly increased the mean flip angle in swine heart from 74.4±6.7% (mean ± standard deviation) to 94.7±4.8% of the desired flip angle and significantly reduced CV from 0.11±0.03 to 0.07±0.02 (p<<1e-10 for both). These results compare well with several previous human studies, except that the mean flip angle in the human heart only improved to 89% with RF shimming, possibly because the RF shimming routine does not consider safety constraints in very large patients. Additionally, mean flip angle decreased and CV increased with larger cross sectional body area, however, the RF shimming parameters did not correlate with cross sectional body area. RF shim power ratio correlated weakly with Right-Left/Anterior-Posterior ratio but phase difference did not, further substantiating the need for subject specific cardiac RF shimming.